2022
DOI: 10.11130/jei.2022.37.3.523
|View full text |Cite
|
Sign up to set email alerts
|

ESG Performance of Multinational Companies and Stock Price Crash: Evidence from Korea

Abstract: Our research focuses on the relationship between the ESG performance of South Korean multinational companies and stock price crash in next year. For our study, we divide samples into three different categories - namely, all companies, multinational companies (MNC) and non-multinational companies(non-MNC). Our major findings are as following. First, we find the negative relationship between the social (S) score of multinational companies and future price crash, indicating that their social performance prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…He et al found that firms with high ESG performance have better risk-taking capacity, and the contribution of ESG performance to corporate risk-taking capacity is more pronounced in firms with lower information transparency and weaker corporate governance [62]. Lee et al concluded that firms with improved ESG performance could significantly reduce the risk of share price crashes [63]. Sciarelli et al argue that integrating ESG criteria, gradually incorporating ESG criteria into corporate financial communications, and improving the accuracy and transparency of disclosure on relevant issues can help make investors' investments more efficient and promote sustainable financial growth [64].…”
Section: Esg Performancementioning
confidence: 99%
“…He et al found that firms with high ESG performance have better risk-taking capacity, and the contribution of ESG performance to corporate risk-taking capacity is more pronounced in firms with lower information transparency and weaker corporate governance [62]. Lee et al concluded that firms with improved ESG performance could significantly reduce the risk of share price crashes [63]. Sciarelli et al argue that integrating ESG criteria, gradually incorporating ESG criteria into corporate financial communications, and improving the accuracy and transparency of disclosure on relevant issues can help make investors' investments more efficient and promote sustainable financial growth [64].…”
Section: Esg Performancementioning
confidence: 99%
“…In the literature review shows that ESG disclosure can mitigate corporate crash risk (Bae et al, 2021;Dumitrescu, and Zakriya, 2021;Hua Fan , and Michalski, 2020;Silva, 2022), both from economic, social and governance aspects which correlate negatively with stock price crash risk (Lee et al, 2022, andLi et al, 2022). Aside from being a crash risk mitigation factor, company involvement and intention in ESG disclosure is related to the type of organizational strategy.…”
Section: Introductionmentioning
confidence: 99%